Cyclic expansion extrusion results in successful consolidation and enhancements in mechanical and physical properties of semi biodegradable Ti-Mg composite implants - Elnaz Gharehdaghi; Faramarz Fereshteh-Saniee (Scientific Reports)
Abstract In the present research work, the cyclic expansion-extrusion (CEE) method which is a simple and effective bulk severe plastic deformation (SPD) technique is used to successfully consolidate titanium-magnesium powder to produce rod implants for biomaterial applications. After insertion of such implant in the body, degradation of Mg and replacement of the bone tissues, its whole mechanical behavior converts much closer to that of the bone. Accordingly, the influences of the processing speed and the number of CEE passes on the consolidated samples were assessed by examining the improvements in density, various mechanical properties and the microstructure of the Ti-Mg products. The compressive strength of the composite rod, made under four different process conditions, ranged from 354.7 MPa to 712.7 MPa, acceptable compared with the values for the human bone. Adding magnesium has caused a reduction in the elastic modulus of the Ti-Mg composite, favorable to avoid the stress shielding. The findings presented in this article have shown that by adjusting the parameters of the CEE process, it is possible to create an implant material with the necessary mechanical properties tailored for specific applications.